Variações estruturais e funcionais da comunidade lenhosa ao longo da sucessão em floresta tropical sazonalmente seca - Oliveira, Clemir Candeia de (2019)
The succession process in seasonally dry tropical forests (FTSSs), which results in changes in vegetation composition and structure, has been well evidenced. As well as, the record of plant species that present persistent populations along the successional gradient. In this study, we sought to answer the following questions. First, how long the composition and structure of the vegetation of FTSSs leads to recover its state of natural. Second, how persistent species respond to different edaphic conditions on successional gradients in these forests. We performed a floristic and phytosociological study in three areas of FTSSs in northeastern Brazil. For each region, we delimited areas chronosequence with the same interval (5, 15, 25, 35 and a reference community aged > 45 years). At each age, we measured 11 structural parameters of the vegetation. In addition, we measured anatomical and structural characteristics of foliar and stem of the persistent species along the chronosequence, as well as collecting physical-chemical characteristics of the soil in the three areas. Only the parameters density of individuals and richness reached similarity with the reference ecosystem at 15 and 35 years, respectively. The most plastic functional characteristics of the persistent species were leaf limb (L), specific leaf area (SLA), leaf thickness (LT), chlorophyll concentration (CC) and hydraulic conductivity (KP). Only L, water saturated content (WSC), and KP were correlated with edaphic characteristics. Therefore, we conclude that the resilience of some parameters does not represent the total similarity of the vegetation with the reference community of FTSS. As well, the plasticity of the persistent species allows to support the environmental variations, being considered good models for the management and reforestation of areas in recovery process in FTSSs.